Psychological features of systemic sclerosis: results from an observational study - Romanazzo, Sara; Rometsch, Caroline; Marangoni, Alessia; Guiducci, Serena; Cosci, Fiammetta (Frontiers in Medicine, 2024)
Objectives: (a) Assessing mental disorders, psychological distress, psychological wellbeing in patients with systemic sclerosis (SSc); (b) identifying psychological features independently contributing to the status of having the diagnosis of SSc.Methods: Two hundred SSc outpatients were compared with 100 healthy subjects. Mental disorders were assessed via the Mini International Neuropsychiatric Interview (MINI). Self-reported rating scales were administered: Health Assessment Questionnaire Disability Index (HAQ-DI), Symptom Checklist-90-Revised (SCL-90-R), Psychological Well Being scales (PWB). General linear models allowed to verify which psychological feature would individually make unique contributions to overall status of having the diagnosis of SSc.Results: Major depressive episode/disorder, panic disorder were more prevalent among patients with SSc (p < 0.05); SCL-90-R somatization and depression were more severe (p < 0.05) in SSc; PWB personal growth, positive relationships with others, purposes in life were poorer (p < 0.05) in patients with SSc if compared to healthy controls. The final general linear model, accounting for 20.4% of variance, showed that having the diagnosis of SSc was associated to lower SCL-90-R paranoid ideation and poorer PWB relationships with others.Conclusions: SSc showed to present psychological features in need of assessment since some of them individually made unique contributions to overall status of having the SSc diagnosis.